Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\left(2^2+4^2+...+100^2\right)-\left(1^2+3^2+...+99^2\right)\)
\(A=2^2-1^2+4^2-3^2+...+100^2-99^2\)
\(A=\left(2-1\right)\left(2+1\right)+\left(4-3\right)\left(4+3\right)+...+\left(100-99\right)\left(100+99\right)\)
\(A=1\left(1+2\right)+1\left(3+4\right)+....+1\left(99+100\right)\)
\(A=1+2+3+4+....+99+100\)
A=5050
\(B=3^8.7^8-\left(21^4-1\right)\left(21^4+1\right)\)
\(B=\left(3.7\right)^8-\left(21^8-1\right)\)
\(B=21^8-21^8+1\)
B=1
mà A=5050
⇒ A>B
Làm dễ hiểu chút
\(A=\left(2^2+4^2+...+100^2\right)-\left(1^2+3^2+...+99^2\right)\)
\(=\left(2^2-1^2\right)+\left(4^2-3^2\right)+...+\left(100^2-99^2\right)\)
\(=\left(2+1\right)\left(2-1\right)+\left(4+3\right)\left(4-3\right)+...+\left(100-99\right)\left(99+100\right)\)
\(=3+7+...+199\)
\(B=3^8.7^8-\left(21^4-1\right)\left(21^4+1\right)\)
\(=21^8-\left(21^8-1\right)=1\)
Vậy A > B
21) 125x3 -1
=125x3-13
=(5x-1)(25x2+5x+1)
22) 4x4 - 9x2
=x2(4x2-9)
=x2(4x2-32)
=x2(2x-3)(2x+3)
23) 64x2 - 25y4
=(8x)2-(5y2)2
=(8x-5y2)(8x+5y2)
24) 4( a + b )2 - 9( a - b )2
=22(a+b)2-32(a-b)2
=[2(a+b)]2-[3(a-b)]2
=[2(a+b)-3(a-b)][2(a+b)+3(a-b)]
=(2a+2b-3a+3b)(2a+2b+3a-3b)
=(5a-b)(5b-a)
25) 8( x + 1 )3 - 27( x - 1 )3
=23(x+1)3-33(x-1)3
=[2(x+1)]3-[3(x-1)]3
={[2(x+1)]-[3(x-1)}{[2(x+1)]2+[2(x+1)]*[3(x-1)]+[3(x-1)]2}
={2x+2-3x+3}{4x2+8x+4+6x2-6+9x2-18x+9}
=(5-x)(19x2-10x+7)
\(\left(2x+1\right)^2-4\left(x+2\right)^2=9\)
\(\left(2x+1\right)^2-\left[2\times\left(x+2\right)\right]^2=9\)
\(\left[\left(2x+1\right)-2\times\left(x+2\right)\right]\left[\left(2x+1\right)+2\times\left(x+2\right)\right]=9\)
\(\left(2x+1-2x-4\right)\left(2x+1+2x+4\right)=9\)
\(\left(-3\right)\left(4x+5\right)=9\)
\(4x+5=\frac{9}{-3}\)
\(4x+5=-3\)
\(4x=-3-5\)
\(4x=-8\)
\(x=-\frac{8}{4}\)
\(x=-2\)
***
\(3\left(x-1\right)^2-3x\left(x-5\right)=21\)
\(3\times\left[\left(x-1\right)^2-x\left(x-5\right)\right]=21\)
\(x^2-2x+1-x^2+5x=\frac{21}{3}\)
\(3x+1=7\)
\(3x=7-1\)
\(3x=6\)
\(x=\frac{6}{3}\)
\(x=2\)
***
\(\left(x+3\right)^2-\left(x-4\right)\left(x+8\right)=1\)
\(\left(x^2+2\times x\times3+3^2\right)-\left(x^2+8x-4x-32\right)=1\)
\(x^2+6x+9-x^2-8x+4x+32=1\)
\(2x=1-9-32\)
\(2x=-40\)
\(x=-\frac{40}{2}\)
\(x=-20\)
bằng phương pháp nào zậy bn????
547675675675678768768789980957457346242645657
giải
a)(x+2)^2+(x-3)^2-2(x-1)(x+1)
x^2+4x+4+x^2-6x+9-2(x^2-1)=9
x^2+4x+4+x^2-6x+9-2x^2+2=9
-2x+15=9
-2x=9-15
-2x=-6
x=-6:(-2)
x=3
d)4(x+1)^2+(2x-1)^2-8(x-1)(x+1)=11
4(x^2+2x+1)+4x^2+4x+1-8(x^2-1)
4x^2+8x+4+4x^2+4x+1-8x^2+8=11
12x+13=11
12x=11-13
12x=-2
x=-1/6
\(3^8\cdot7^8-21^8+1=21^8-21^8+1=1\)